If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -5)(5 + 5) = 0 Reorder the terms: (-5 + y)(5 + 5) = 0 Combine like terms: 5 + 5 = 10 (-5 + y)(10) = 0 Reorder the terms for easier multiplication: 10(-5 + y) = 0 (-5 * 10 + y * 10) = 0 (-50 + 10y) = 0 Solving -50 + 10y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '50' to each side of the equation. -50 + 50 + 10y = 0 + 50 Combine like terms: -50 + 50 = 0 0 + 10y = 0 + 50 10y = 0 + 50 Combine like terms: 0 + 50 = 50 10y = 50 Divide each side by '10'. y = 5 Simplifying y = 5
| 8+3(6+4)= | | .5(6x+4)=x+2(x+1) | | 3(7x-2)+5=26 | | 15=3n+6p | | -4w+8=2w+44 | | x=5+4y | | 4x=7x-2 | | (7p+8)+(2p-3)= | | 2x-3=9-x | | 4544=71a | | -4x-4=-8 | | y+3+8=180 | | 2x-5+8=180 | | -3b=-33 | | 5+3a=17 | | 7+3a=16 | | 4(x-2)=5(x-1)+3x+2 | | (7p+8)(2p-3)=9p+5 | | (-362)+421= | | 8+3a=17 | | 4n+11-6n+8m=36 | | -6s=6s-144 | | x-(-19)=-20 | | 3(x-9)-4(3x+1)=x-33 | | 15x-7=8x | | b^4-16a^4=0 | | 3x-6y=-6x+34 | | 4.7x-5.48=11.44 | | (K+2)(6k-7)=0 | | x=ax+1a+bx-2b | | 12-3x+9x=14+6x | | 5x^2+4xy+2y^2=6 |